2023
DOI: 10.21203/rs.3.rs-2493187/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Spatial and Temporal Trend for Hydro-climatic Parameters in the Kilombero River Catchment, Tanzania

Abstract: Perceived and real-life water availability have raised social and economic conflicts that necessitate proper water management. This requires an understanding of spatial-temporal trends of hydro-climatic variables as the main contributor to available water for use by sectors of economy. In this study, we have analyzed the trend of hydro-climatic variables viz. precipitation, temperature, evapotranspiration and river discharge. One downstream river gauge station was used for discharge data whereas a total of 9 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Commonly, rainfall was seen to be decreasing during the months of May, June, July and September while there was an increase in rainfall for the months of March, August, April, December, November and October for extended time (Smith, 2016). The results agreed with Senkondo, (2020) and Sigalla et al, (2023) which indicated that rainfall had shown a steady decrease in past ten years. Further, the aerial rainfall varies by more than 200mm in an analysis done for 40 years in areas.…”
Section: Findings and Discussion Aerial Precipitation Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…Commonly, rainfall was seen to be decreasing during the months of May, June, July and September while there was an increase in rainfall for the months of March, August, April, December, November and October for extended time (Smith, 2016). The results agreed with Senkondo, (2020) and Sigalla et al, (2023) which indicated that rainfall had shown a steady decrease in past ten years. Further, the aerial rainfall varies by more than 200mm in an analysis done for 40 years in areas.…”
Section: Findings and Discussion Aerial Precipitation Analysissupporting
confidence: 89%
“…The long rains fall between Januarys to May, whereas the short rains fall between Octobers to December. Similarly, Sigalla et al, (2023) and Kangalawe and Liwenga, (2015), showed the average rainfall within Kilombero basin range between 1000mm to 1400mm where the reported month of high rainfall intensity is April. It was only the month of April that showed the peak flow from 1989 to 2020.…”
Section: Findings and Discussion Aerial Precipitation Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…This paradigm shift requests a re-evaluation of conventional hydrological models. It underlines the need for robust trend analysis methods, such as the Mann-Kendall (MK) test, to detect and interpret these changes (Sigalla, Valimba et al 2023). The MK test is known for its robustness in identifying trends in hydrological time series, and it is widely employed in various hydro-meteorological analyses.…”
Section: Introductionmentioning
confidence: 99%